Citizenship Policies for an Age of Migration - Aleinikoff, T. Alexander (Book collections on Project MUSE., 2011)
Many liberal democracies, facing high levels of immigration, are rethinking their citizenship policies. In this book, a group of international experts discuss various ways liberal states should fashion their policies to better accommodate newcomers. They offer detailed recommendations on issues of acquisition of citizenship, dual nationality, and the political, social, and economic rights of immigrants. Contributors include Patrick Weil (University of Paris Sorbonne), David A. Martin, (University of Virginia School of Law), Rainer Bauböck, (Austrian Academy of Sciences), and Michael Fix (Urban.